Correlation between morphofunctional state of esophageal and forestomach mucous membranes in patients with erosive form of gastroesophageal reflux disease - Markovskiy, V.D.; Gargin, V.V.; Sakal, V.V. (Pathologia, 2013)
We examined patients with symptoms of gastroesophageal reflux disease. Interconnection between morphofunctional state of esophageal and forestomach mucous membranes in patients with erosive form of gastroesophageal reflux disease was investigated. Microscopically esophagitis and gastritis were identified by necrosis/erosion presence, neutrophil/lymphocyte intraepithelial infiltration, basal cell hyperplasia, elongation of papillae.